SEBARAN UNSUR HARA N, P, K DAN PH DALAM TANAH - Bambang Siswanto (BUANA SAINS, 2018)
Soil nutrient availability maps are needed to be used as a basis for managing fertilizer use, as well as soil acidity (pH) values. If the nutrient status of N, P, K and soil acidity is known, it is expected that the dosage of fertilization of each land can be done in accordance with thenutrient status. It can also reduce the cost of fertilization. This study aims to determine the factors of land affecting the distribution of nutrients N P K and soil pH. The research was conducted in Gugut Village, Rambipuji District, Jember from June to August 2016. The research was conducted by using free grid survey method with semi-detailed survey rate of 1: 25.000 scale. The distribution pattern of each nutrient status was analyzed by matrix method approach to find out the factors that most influence the distribution of nutrients N, P, K and pH.  From the result of research, map of nutrient distribution of N, P, K is almost similar to the result of geological map overlay, landform, land use and altitude. According to Wilding and Drees (1983), the diversity of nutrient status can be due to differences in lithology / parent material, climate, erosion, biological influences, and hydrology. The N, P, K soil availability map only meets 32.76% of the elevation map section. Therefore, the temporal nutrient status mapping can not be generated based on existing land map units so it is advisable to use the rigid grid method. While soil pH maps are almost similar to overlays between geological maps, landforms, land use and climate.